Photodynamic therapy as an adjunct to periodontal treatment: literature review (Research, Society and Development, 2021)
Periodontal disease is a chronic inflammatory process of infectious character which affects the tooth support tissues and can lead to tooth loss. Acting as an adjuvant in the treatment of periodontal diseases, the Phodynamic Therapy has gained visibility. This work aims to address the application of this procedure in periodontal treatment, its advantages and disadvantages, indications and contraindications, concept of the technique, materials used and clinical results. The methodology used consisted of a literature review, which was conducted by accessing the PubMed database and the VHL Regional Portal, with publications selected between 1993 and 2021, using keywords on the subject. The technique consists in the association of a light source and a photosensitizer, for the purpose of promoting microbial death, disinfection and assist in the healing process. Research confirms several advantages of its application in dental practice such as for example the inability to generate bacterial resistance and harmful side effects as well as, promotes localized action, affordability and ease of management. Studies demonstrate the effectiveness of this therapy against periodontopathogenic bacteria and their positive results when applied as an aid in periodontal treatment, as it allows the elimination of retained pathogens in areas of furcation grooves, concavities, distal areas of the molars and deep periodontal pockets, which because of the limitation of the mechanical treatment, they end up remaining and recolonizing those places. The future perspective is that photodynamic therapy will gain more space in the clinical performance, being a promising adjuvant in obtaining satisfactory results in periodontics.